Co-production in health policy and management: a comprehensive bibliometric review - Floriana Fusco; Marta Marsilio; Chiara Guglielmetti (BMC, 2020)
Abstract Background Due to an increasingly elderly population, a higher incidence of chronic diseases and higher expectations regarding public service provision, healthcare services are under increasing strain to cut costs while maintaining quality. The importance of promoting systems of co-produced health between stakeholders has gained considerable traction both in the literature and in public sector policy debates. This study provides a comprehensive map of the extant literature and identifies the main themes and future research needs. Methods A quantitative bibliometric analysis was carried out consisting of a performance analysis, science mapping, and a scientific collaboration analysis. Web of Science (WoS) was chosen to extract the dataset; the search was refined by language, i.e. English, and type of publication, i.e. journal academic articles and reviews. No time limitation was selected. Results The dataset is made up of 295 papers ranging from 1994 to May 2019. The analysis highlighted an annual percentage growth rate in the topic of co-production of about 25%. The articles retrieved are split between 1225 authors and 148 sources. This fragmentation was confirmed by the collaboration analysis, which revealed very few long-lasting collaborations. The scientific production is geographically polarised within the EU and Anglo-Saxon countries, with the United Kingdom playing a central role. The intellectual structure consists of three main areas: public administration and management, service management and knowledge translation literature. The co-word analysis confirms the relatively low scientific maturity of co-production applied to health services. It shows few well-developed and central terms, which refer to traditional areas of co-production (e.g. public health, social care), and some emerging themes related to social and health phenomena (e.g. the elderly and chronic diseases), the use of technologies, and the recent patient-centred approach to care (patient involvement/engagement). Conclusions The field is still far from being mature. Empirical practices, especially regarding co-delivery and co-management as well as the evaluation of their real impacts on providers and on patients are lacking and should be more widely investigated.